Dampak Intervensi Pemerintah Terhadap Ekspor di Indonesia - Bellen Kusuma Handika; Kamila Lintang Pratiwi; Raudya Prameswari (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to analyze various forms of government intervention in export activities in Indonesia, and assess their impact on the country's economy. In the context of ever-changing international trade, the Indonesian government is faced with a major challenge in maintaining economic stability, one of which is through export policy. This study shows how government intervention affects export performance, as well as identifying the consequences that arise after the implementation of such policies.